The Amazon basin in transition - Davidson, Eric Aa; Araüjo, Alessandro Carioca de; Artaxo, Paulo; Balch, Jennifer K.; Brown, Irving Foster; Bustamante, Mercedes M.C.; Coe, Michael T.; DeFries, Ruth S.; Keller, Michael; Longo, Marcos; Munger, J. William; Schroeder, Wilfrid; et al. (Nature, 2012)
Agricultural expansion and climate variability have become important agents of disturbance in the Amazon basin. Recent studies have demonstrated considerable resilience of Amazonian forests to moderate annual drought, but they also show that interactions between deforestation, fire and drought potentially lead to losses of carbon storage and changes in regional precipitation patterns and river discharge. Although the basin-wide impacts of land use and drought may not yet surpass the magnitude of natural variability of hydrologic and biogeochemical cycles, there are some signs of a transition to a disturbance-dominated regime. These signs include changing energy and water cycles in the southern and eastern portions of the Amazon basin. © 2012 Macmillan Publishers Limited. All rights reserved.
Keywords: Carbon Dioxide; Nitrogen; Agricultural Practice; Biogeochemical Cycle; Climate Variation; Deforestation; Drought Stress; Energy Budget; Environmental Disturbance; Forest Fires; Hydrological Change; Land-use Change; Precipitation (climatology); River Discharge; Water Budget; Agriculture; Atmosphere; Carbon Storage; Climate Change; Deforestation; Drought; Energy Balance; Greenhouse Gas; Priority Journal; Review; River; Seasonal Rain Forest; Carbon Cycle; Climate Change; Droughts; Ecosystem; Fires; Forestry; Rain; Rivers; Seasons; Trees; Amazon Basin